The viscosity of nontraditional lightweight completion fluid at elevated temperature and pressure - Khalil, M.; Jan, B.M.; Abdul Raman, Abdul Aziz (Taylor & Francis Group, 2012)
Experimental viscosity values of nontraditional lightweight completion fluid at pressure and temperature ranges of 0.1 MPa to 4.48 MPa, and of 25ıC to 100ıC, respectively, were reported. To establish the relationship among viscosity, pressure, and temperature, experimental data were fit to the modification of Mehrotra and Svrcek’s equation. The result shows that the model could be used to describe the fluid viscosity over a wide range of pressure and temperature. The calculated what is sum of square error and root mean square error are 0.2135 and 0.08892, respectively. It is also shown that the predicted values from the model are in a good agreement with both the experimental values and field data.